Evaluation of sustainable airport development strategies using an integrated intuitionistic fuzzy decision-making method and unknown weights - Fei Gao (Alexandria Engineering Journal, 2025)
Air transportation, while highly efficient for passenger transit, poses a substantial challenge due to its significant contribution to carbon emissions, and there has been a burgeoning interest in sustainable airports as a means to attain environmental sustainability. However, evaluating and prioritizing appropriate development strategies for sustainable airports has emerged as a complex challenge. To this end, this study introduces an integrated intuitionistic fuzzy decision-making approach for sustainable airport development strategy evaluation. Firstly, an integrated criterion weight calculation method is employed, extending the step-wise assessment ratio analysis (SWARA) by incorporating intuitionistic fuzzy sets (IFSs) to determine subjective weights, while the intuitionistic fuzzy weights by envelope and slope (IF-WENSLO) technique is applied for objective weight computation. Subsequently, the preference ranking organization method for enrichment of evaluations (PROMETHEE) is integrated with IFSs to effectively select sustainable airport development strategies. To demonstrate the effectiveness of the proposed method, it is applied to a practical case in China. The results affirm the reliability and rationality of the approach, a validation achieved through sensitivity and comparative analyses. In conclusion, this study presents a novel and efficient methodology for the evaluation and prioritization of sustainable airport development strategies, offering valuable applications and insights for industry practitioners.